2017
DOI: 10.3233/jad-161295
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Insufficiency and Cognitive Function Trajectories in Older Adults: The Rancho Bernardo Study

Abstract: Background Evidence of a role for vitamin D (VitD) in cognitive aging is mixed and based primarily on extreme VitD deficiency. We evaluated the association of VitD insufficiency with cognitive function in older, community-dwelling adults living in a temperate climate with year round sunshine. Methods A population-based longitudinal study of 1058 adults (median age 75; 62% women) who had cognitive function assessed and serum levels of 25-hydroxyvitaminD (25OHD) measured in 1997–99 and were followed for up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 53 publications
1
28
0
2
Order By: Relevance
“…However, most studies did not consider confounders like depression. Four studies [9,22,23,25] found no association between low serum vitamin D levels and CI and dementia in a longitudinal follow-up, whereas two studies [21,24] found a significant association (P � 0.001). However, the studies which found a significant association were smaller in size and duration of follow-up.…”
Section: Evidence Through Cross-sectional and Longitudinalmentioning
confidence: 93%
See 3 more Smart Citations
“…However, most studies did not consider confounders like depression. Four studies [9,22,23,25] found no association between low serum vitamin D levels and CI and dementia in a longitudinal follow-up, whereas two studies [21,24] found a significant association (P � 0.001). However, the studies which found a significant association were smaller in size and duration of follow-up.…”
Section: Evidence Through Cross-sectional and Longitudinalmentioning
confidence: 93%
“…Nevertheless, the issue of reverse causality remains to be answered [21]. Table 1 shows a summary of evidence demonstrating an association between serum 25(OH)D, CI, and dementia [9,21,22,[23][24][25][26]. Many studies have shown an association of low vitamin D with CI at a cross-sectional level although the same studies with longitudinal follow-ups did not replicate the association [21,23,24].…”
Section: Evidence Through Cross-sectional and Longitudinalmentioning
confidence: 99%
See 2 more Smart Citations
“…So much of what she pioneered is now so well established in mainstream epidemiologic research that it may be difficult to realize how groundbreaking her approach was at the time. She was one of the earliest researchers to illustrate the scientific value of examining in a population a broad range of physiologic measures and biomarkers such as glucose metabolism, sex hormones, thyroid function, and cytokines; detailed lifestyle factors including diet and physical activity; psychosocial factors such as depression, the role of social status, education, and stress; and new phenotypes including clinical measurements of eyes and bones, as well as functional health (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). She recalls that one of the comments at the time was "Why would you want to study normal people?"…”
Section: The Rancho Bernardo Studymentioning
confidence: 99%